A Reduction in Video Gaming Time Produced a Decrease in Brain Activity - Gong, Diankun; Yao, Yutong; Gan, Xianyang; Peng, Yurui; Ma, Weiyi; Yao, Dezhong (Frontiers in Human Neuroscience, 2019)
This study examines whether a decrease in brain development is observable after players have reduced their video gaming time over a period of one year. Both video gaming experts and non-experts were recruited, whose resting-state fMRI data were collected at the beginning and the end of the study. Immediately after the first scan, the participants were instructed to spend no smore than three hours on video gaming weekly for one year. The results showed decreased self-reported video gaming skills and decreased amplitude of low-frequency fluctuation in the experts at the end of the study, demonstrating that a reduction in video gaming time over a period of one year produced a decrease in brain development. The non-experts served as a control group and had no significant changes. The findings support the adaptive effect of video gaming experience on brain and cognitive development.